2007
DOI: 10.1007/s10404-007-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow behaviors in an obstacle-type valveless micropump by micro-PIV

Abstract: In this paper, a PZT micropump excited by amplified squarewave signals with various frequencies was used to study the transient flow behaviors in an obstacletype valveless micropump. A micro-particle-image-velocimetry (micro-PIV) with an external trigger was developed to obtain flow fields at the outlet and around the obstacle with various phases in a cycle. In comparison with previous studies on the pump performance, such as pump pressure and volume flow rate, more detailed information about the pump was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Therefore, the efficiency for generating net flow per cycle must be raised. However, the results in our previous study (Sheen et al 2008) have confirmed that the efficiency for generating net flow is low in an obstacle-type valveless micropump using a micro-Particle-Image-Velocimetry (micro-PIV) system.…”
Section: Introductionsupporting
confidence: 66%
“…Therefore, the efficiency for generating net flow per cycle must be raised. However, the results in our previous study (Sheen et al 2008) have confirmed that the efficiency for generating net flow is low in an obstacle-type valveless micropump using a micro-Particle-Image-Velocimetry (micro-PIV) system.…”
Section: Introductionsupporting
confidence: 66%
“…This is in contradiction with the results of the steady flow regime where g decreases with increasing Re. • For the total pump, net flow rate increases with increasing Re, regardless the diffuser angle (Tanaka et al 2008;Sheen et al 2008;Hwang et al 2008). …”
Section: Effects Of Reynolds Numbermentioning
confidence: 93%
“…Experimental investigations of the unsteady flow in a microdiffuser were performed by Sheen et al (2008). They measured the transient flow behavior in an obstacle-type valveless PZT micropump using a micro-PIV for excitation frequencies in the range 1 kHz B f B 3 kHz.…”
Section: Flow Separationmentioning
confidence: 99%
“…The net flow rate obtained was nearly independent of h, for h [ 35°. Experimental investigations of the unsteady flow in a diffusernozzle element were performed by Sheen et al (2008). They measured the transient flow behavior in an obstacle-type valveless PZT micropump using a micro-PIV for excitation frequencies in the range 1 kHz B f B 3 kHz.…”
Section: Introductionmentioning
confidence: 99%